Biochemical and biophysical characterization of water-soluble pectin from Opuntia ficus-indica and its potential cytotoxic activity. (October 2018) - Lefsih, Khalef; Giacomazza, Daniela; Passantino, Rosa; Costa, Maria Assunta; Bulone, Donatella; Mangione, Maria Rosalia; Guarrasi, Valeria; Mingoia, Francesco; San Biagio, Pier Luigi; Madani, Khodir
Abstract: This work aims to fill the gap in the present knowledge about the structure of pectin from Opuntia ficus-indica . The water-soluble pectin (WSP) fraction, extracted with the Microwave Assisted Extraction (MAE), was further deproteinated (dWSP) and analyzed through several biophysical and biochemical techniques. HPSEC, light scattering and FTIR data showed that dWSP is low methylated high molecular weight pectin. The biochemical structure of dWSP, after methanolysis, silylation, carboxyl reduction showed that dWSP belongs to rhamnogalacturonan I class. Then, dWSP was heat-modified (HM) to obtain small-molecular weight deproteinated fraction (HM-dWSP). Both species, dWSP and HM-dWSP, were tested in LAN5 and NIH 3T3 model cells to study their biological effect. Results indicated that both dWSP and HM-dWSP exerted cytotoxic activity affecting selectively LAN5 cancer cells, without any effect on NIH 3T3 normal cells. Graphical abstract: Highlights: The dWSP is a rhamnogalacturonan backbone with glucan and galactan sidechains. dWSP is high molecular weight low methylated pectin. dWSP and HM-dWSP show a potential cytotoxicity in LAN5 human neuroblastoma cells. No cytotoxic effect was observed in NIH-3T3 normal cells.